2001
DOI: 10.1093/nar/29.6.1373
|View full text |Cite
|
Sign up to set email alerts
|

The N- and C-terminal regions of RBP-J interact with the ankyrin repeats of Notch1 RAMIC to activate transcription

Abstract: The evolutionarily-conserved DNA-binding protein RBP-J directly interacts with the RAM domain and the ankyrin (ANK) repeats of the Notch intracellular region (RAMIC), and activates transcription of downstream target genes that regulate cell differentiation. In vitro binding assays demonstrate that the truncated N- and C-terminal regions of RBP-J bind to the ANK repeats but not to the RAM domain. Using an OT11 mouse cell line, in which the RBP-J locus is disrupted, we showed that RBP-J constructs mutated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 35 publications
5
50
0
Order By: Relevance
“…The PPD binding site is bipartite, with its two elements redundant in most experimental contexts, explaining why it has previously been difficult to identify by mutation or deletion. The previously described requirement for the ANK repeats in CSL-dependent Notch signaling (15,25,36) is consistent with our data showing that the presence of the ANK repeats greatly increases the effectiveness of Su(H) binding to PPD. Perhaps ANK holds PPD in a conformation that is favorable for Su(H) binding.…”
Section: Both Su(h) Binding Regions Contribute To Notch Activity In Vsupporting
confidence: 93%
See 2 more Smart Citations
“…The PPD binding site is bipartite, with its two elements redundant in most experimental contexts, explaining why it has previously been difficult to identify by mutation or deletion. The previously described requirement for the ANK repeats in CSL-dependent Notch signaling (15,25,36) is consistent with our data showing that the presence of the ANK repeats greatly increases the effectiveness of Su(H) binding to PPD. Perhaps ANK holds PPD in a conformation that is favorable for Su(H) binding.…”
Section: Both Su(h) Binding Regions Contribute To Notch Activity In Vsupporting
confidence: 93%
“…It has been suggested that Su(H) may interact in vitro with the ankyrin repeats of Drosophila Notch (24), and indeed, in contrast to the RAM domain, the ANK repeats are essential for all CSL-dependent Notch functions in all studied organisms. However, the binding of CSL proteins to the ANK region seems to be very much weaker than the binding to the RAM domain (25) and has not even been detectable in all studies. Moreover, no CSL binding site has been specifically mapped to this part of the protein.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…In complementary experiments, we examined Notch1 mutants, in which a substantial portion of the Notch1 gene is deleted [amino acids 1056[amino acids -2049[amino acids (Conlon et al, 1995]. This deletion encompasses RAM and Ankyrin repeats required for RBPJκ signaling (Conlon et al, 1995;Fortini and Artavanis-Tsakonas, 1994;Kurooka et al, 1998a;Kurooka et al, 1998b;Lamar et al, 2001;Nam et al, 2003;Tani et al, 2001). We confirmed that posterior hindbrain patterning was normal in Notch1 mutants by assaying for Hoxb1, Fgf3 and Krox20 expression (see Fig.…”
Section: Developmentmentioning
confidence: 69%
“…(For review, see Weinmaster 2000; Panin and Irvine 1998). This fragment is transported to the nucleus via its two NLS elements, where it can then interact with RBP-J (CSL) via its N-terminal RAM domain and adjacent ankyrin-like repeats (Tani et al 2001). This interaction is thought to occur primarily via binding to the central (repressive) domain of RBP-J (Hsieh and Hayward 1995), one of the two regions we have found to mediate interaction with RTA (Fig.…”
Section: Discussionmentioning
confidence: 99%